2016
DOI: 10.1139/er-2015-0081
|View full text |Cite
|
Sign up to set email alerts
|

A review of sources, levels, and toxicity of polybrominated diphenyl ethers (PBDEs) and their transformation and transport in various environmental compartments

Abstract: Polybrominated diphenyl ethers (PBDEs) are a group of organobromine compounds that are used as flame retardants in many commonly used products. Their presence has been confirmed in various environmental matrices. Their usage in numerous consumer products has lent credence to their ability to retard flammable gas formation, hence their ubiquitous nature in the environment. PBDEs have been described as endocrine disrupting chemicals because of their interference with the endocrine system function in fish and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 221 publications
0
23
0
3
Order By: Relevance
“…Other groups of chemicals, such as persistent organic pollutants (POPs), are of concern due to their persistence, bioconcentration and biomagnification effects [9]. Finally, a growing concern about the relation between pollution, and toxic algal communities has arisen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other groups of chemicals, such as persistent organic pollutants (POPs), are of concern due to their persistence, bioconcentration and biomagnification effects [9]. Finally, a growing concern about the relation between pollution, and toxic algal communities has arisen.…”
Section: Introductionmentioning
confidence: 99%
“…One of the challenges to accomplish the required aim was to be able to simultaneously detect and quantify different families of chemical contaminants with minimum or without any sample preparation, at very low concentration levels, on a device able to work autonomously in situ (ocean, aquaculture facilities, etc). In the last years a variety of multiresidue chromatographic methods, usually coupled to tandem mass spectrometry showing high specificity and sensitivity have been reported (LC-MS/MS or GC-MS/MS) [9,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Though some highly-toxic PBDEs have been banned in many countries, other PBDEs with relatively lower toxicity, such as BDE-209, are still largely produced and used in the world (Chen et al, 2012;Akortia et al, 2016). Although the concentration of PBDEs in the human blood is generally low in most places, it has been reported that the concentrations of PBDEs in the human blood of workers can reach significantly high levels in many heavily polluted areas (Jin et al, 2009;Makey et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(5) E U R A C H E M / C I TA C , 2 0 0 3 , " T r a c e a b i l i t y i n c h e m i c a l measurement: A guide to achieving comparable results in chemical measurement"; (1,4). Senyawa ini digunakan sebagai flame retardant yaitu zat aditif yang ditambahkan dalam material atau bahan agar memenuhi standar legitimasi sifat flammable (mudah terbakar) (7), dengan tujuan untuk membuat suatu material menjadi lebih tahan terhadap api.…”
Section: Daftar Pustakaunclassified
“…Validasi metode pengukuran gas dengan peralatan gas analyzer dilakukan secara perbandingan langsung dengan certified span gas (CSG) yang tertelusur ke sistem satuan internasional melalui rantai perbandingan yang tidak terputus [2][3][4][5]. Adapun lingkup validasi metode pengukuran meliputi gas O 2 , CO, NO, NO 2 , SO 2 , CH 4 dan H 2 S yang ditentukan nilai accuracy, repeatability atau stability, linearity dan calibration and measurement capability (CMC).…”
unclassified